2021
DOI: 10.1111/avsc.12624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inter‐annual meteorological fluctuations and wild boar disturbance on the vegetation of Mediterranean temporary ponds

Abstract: Questions Which are the effects of inter‐annual meteorological fluctuations on plant species richness and vegetation dynamics in Mediterranean temporary ponds, shallow wetlands characterized by alternating phases of drought and flooding? Which are the effects of wild boar disturbance? How do the responses of specialist or non‐specialist species of the habitat differ? Location NW Sardinia Island (Italy). Methods We assessed plant cover during six years within one 60 cm × 60 cm quadrat in each of five areas. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
5
4
1
Order By: Relevance
“…Generalist species are the ecological types that dominated in large SWEs, whereas, in small and undisturbed SWEs, generalist and specialist species achieved the same average coverage values. This finding differs from that reported in Caria et al [18], which showed that specialist species had the highest overall cover, in addition to being significantly higher in disturbed than in not-disturbed areas. It is noteworthy that, despite such differences in the coverage, specialist species recorded similar values in both different sizes and treatments of SWEs.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Generalist species are the ecological types that dominated in large SWEs, whereas, in small and undisturbed SWEs, generalist and specialist species achieved the same average coverage values. This finding differs from that reported in Caria et al [18], which showed that specialist species had the highest overall cover, in addition to being significantly higher in disturbed than in not-disturbed areas. It is noteworthy that, despite such differences in the coverage, specialist species recorded similar values in both different sizes and treatments of SWEs.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, the main biological form recorded in both large and small SWEs was therophytes, in agreement with previous studies [43]. In these environments, in fact, the cover of therophytes is linked to their very short life cycles, which are considered an adaptation to survive fluctuations in water availability [18,44,45]. Conversely, differences in coverage of biological form were found based on the level of disturbance; in undisturbed areas, the therophytes dominated, whereas, in disturbed and over-disturbed situations, hemicryptophytes reached the main cover percentage, slightly exceeding the value of therophytes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations